A Genetic Analysis of Solanum aethiopicum Gilo Genotypes for Germination and Seedling Growth - Shamim Birungi (Uganda Christian University, 2025)
Despite the significance of S. aethiopicum Gilo. Limited data on genetic variation influencing germination and seedling growth in Solanum aethiopicum Gilo constrain breeding programs for crop yield and quality improvement. This study investigated Genetic variation and Inheritance of germination and seedling growth in S. aethiopicum Gilo, with G3, G11, and their F1 hybrid (G3 × G11). A completely randomized design was employed to evaluate germination percentage, cotyledon size, and seedling vigor among others. Findings showed significant differences (p < 0.005) among genotypes for all the traits. The hybrid (G3 × G11) showed the highest germination percentage (60.08%) and germination velocity index (9.85), while G11 had the lowest in both. G11 exhibited the longest mean germination time (7.71 days), whereas the hybrid had the shortest (6.30 days). G3 generally had the highest cotyledon height, width, and seedling height, while G11 had the lowest. Seedling vigor, leaf length, and leaf width were highest in the hybrid and lowest in G3. The hybrid also had the highest number of leaves compared to G3. Inheritance analysis revealed Broad Sense Heritability with additive gene above (70-90%) contributing to early seedling traits, and non-additive of (20-40%) effects on germination. These findings of the study concur with studies done in S. lycopersicum and S. melongena where hybrid vigor and polygenes control early development. More molecular research should be conducted to identify markers related to seedling vigor, hence accelerating genetic enhancement of this underutilized crop.
Undergraduate